Blue skies and red seas : how the Faroese see their nation portrayed in international media - Metheny, Miranda (University of Missouri--Columbia, 2014)
Professional project report submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Journalism from the School of Journalism, University of Missouri--Columbia. Media representation of the Faroe Islands, like that of other small, little-known places, is vulnerable to being skewed by various frames, agendas and biases. The islanders are demonized by the anti-whalers and their world portrayed as uniformly picturesque and exotic by the tourism industry. Nearly all representations of the Faroes exoticize the nation, relying on old-fashioned stereotypes, historical details, and extreme exceptions while neglecting to portray many aspects of the everyday reality for most Faroese. This analysis, based on interviews and photo elicitation with a variety of Faroese nationals as well as journalists covering Faroese issues, explores how the Faroese feel about their portrayal in the international media and considers the various factors that encourage this sort of exotification. The professional work project consists of photography and writing on topics ranging from the current gender disparity and the lives of modern Faroese women to learning Faroese as an outsider and the various summer festivals on the islands, all produced with the intention of creating a balanced and well-rounded image of the modern Faroese nation.